2005
DOI: 10.3354/meps294079
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced habitat shifts and energetic consequences in Atlantic croaker and brown shrimp on the Gulf of Mexico shelf

Abstract: Seasonal, summertime hypoxia (dissolved oxygen ≤ 2 mg l -1 ) has occurred over large areas (~1000 to 20 000 km 2 ) of the northwestern Gulf of Mexico shelf during several years since at least the mid-1980s, resulting in habitat loss for demersal species. To evaluate the effects of hypoxiainduced habitat loss on Atlantic croaker Micropogonias undulatus and brown shrimp Farfantepenaeus aztecus, we compared species' spatial distributions and relationships to abiotic factors (temperature, dissolved oxygen, salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 66 publications
2
102
1
Order By: Relevance
“…The hypothesized outcome-that female Atlantic Croakers from a system characterized by severe hypoxia (Rappahannock River) would exhibit lower mean ovarian lipid content than females from a mildly hypoxic system (York River)-was supported. We also observed that within the Rappahannock River, catches of Atlantic Croakers were greater from normoxic habitats than from hypoxic habitats, indicating that habitat shifts can occur even for a relatively hypoxia-tolerant species (Bell and Eggleston 2005;Craig and Crowder 2005).…”
Section: Discussionmentioning
confidence: 61%
“…The hypothesized outcome-that female Atlantic Croakers from a system characterized by severe hypoxia (Rappahannock River) would exhibit lower mean ovarian lipid content than females from a mildly hypoxic system (York River)-was supported. We also observed that within the Rappahannock River, catches of Atlantic Croakers were greater from normoxic habitats than from hypoxic habitats, indicating that habitat shifts can occur even for a relatively hypoxia-tolerant species (Bell and Eggleston 2005;Craig and Crowder 2005).…”
Section: Discussionmentioning
confidence: 61%
“…While lab experiments demonstrate that hypoxia slows down shrimp growth and delays molting, and mortality is a limiting case if hypoxia is severe enough, there is a countervailing force at play to limit the effect in the fishery. In particular, marine ecologists have shown that shrimp tend to congregate on the edges of hypoxic areas, making them easier to catch (Craig and Crowder 2005;Craig 2012). These forces raise questions about the net effect of hypoxia on the shrimp fishery.…”
Section: In This Article We Analyze the Gulf Of Mexico Brown Shrimp mentioning
confidence: 99%
“…Whether there are sufficiently large hypoxic (or anoxic) areas within the spatio-temporally varying Gulf of Mexico Dead Zone to affect shrimp mortality is an open question. The catchability effect follows empirical work showing aggregation of shrimp, other fished species, and fishing vessels along edges of the hypoxic zone in Gulf of Mexico (Craig and Crowder 2005;Craig 2012). The growth effect is consistent with experiments that show slowed lipid uptake and delayed molting in shrimp that are exposed to low oxygen (Craig 2012).…”
Section: A Spatial-dynamic Bioeconomic Simulation Modelmentioning
confidence: 99%
“…Laboratory and field studies in the Neuse River Estuary indicate that brown shrimp have an avoidance threshold of l-2 mg/l dissolved oxygen (Wannamaker and Rice 2000;Eby and Crowder 2002). Furthermore, brown shrimp appear to avoid severely low oxygen levels, but aggregate at high densities in areas of "moderately low dissolved oxygen" (1.6 to 3.7 mg/l) near hypoxic edges (Craig and Crowder 2005;Craig 2012). These results suggest that behavioral changes and resulting shifts in spatial distribution could have energetic consequences and alter trophic interactions that ultimately have consequences for commercial harvest.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…For harvested species, all of these impacts reduce the biomass available for harvest and are expected to be costly to fisheries. Individuals also move to avoid hypoxia, which can lead to aggregations along the edges of hypoxic zones (Craig and Crowder 2005;Craig 2012). Aggregation effects might actually benefit fisheries in the short run by increasing catchability, but movement away from hypoxic zones still requires energy that could otherwise be used for growth and reproduction.…”
Section: Introductionmentioning
confidence: 99%